Cap-binding complex (CBC) - Gonatopoulos-Pournatzis, Thomas (Portland Press Ltd., 2013)
The 7mG (7-methylguanosine cap) formed on mRNA is fundamental to eukaryotic gene expression. Protein complexes recruited to 7mG mediate key processing events throughout the lifetime of the transcript. One of the most important mediators of 7mG functions is CBC (cap-binding complex). CBC has a key role in several gene expression mechanisms, including transcription, splicing, transcript export and translation. Gene expression can be regulated by signalling pathways which influence CBC function. The aim of the present review is to discuss the mechanisms by which CBC mediates and co-ordinates multiple gene expression events.